Requisitos para o reconhecimento contábil de crédito fiscal federal decorrente de ação judicial - Taveira, Larissa (2021)
Scope of the study: This work aims to identify the requirements for the accounting recognition of an asset, specifically of a federal tax credit resulting from a lawsuit, and correlate them with the characteristics of a final decision, in order to identify the right moment and the appropriate amount to the accounting recognition. Method: This is an exploratory research with a qualitative approach. As for data collection, it was carried out based on a bibliographic survey (books, articles, legislation and accounting standards) and the application of a questionnaire to lawyers, accountants and auditors. Through discursive textual analysis, we sought to group the answers obtained and find answers to the objective of the study. Results: The requirements for accounting recognition of the federal tax credit resulting from a final and unappealable lawsuit were identified, identifying the time and the appropriate amount for the purposes of its registration. Thus, a flowchart of the accounting recognition of a tax credit resulting from a final and unappealable lawsuit was prepared. Practical implications / Contributions: As practical implications, there is the possibility of greater compliance in the adoption of accounting practices, increasing the comparability of financial statements and improving the quality of accounting information, since it allows greater predictability in relation to the recognition of values arising from unappealable lawsuits. Thus, it contributes to the academy, adding information to studies in the accounting and tax area, as well as to the business environment, clarifying the analysis and determination of the moment and amount of the tax credit to be recognized in the accounting, arising from lawsuits final and unappealable Impacts: As technological products resulting from this work, there are: a conclusive technical report, whose impact is social, since the results are directed to companies, covering, primarily, the organizational dimension; and a flowchart of the accounting recognition of a tax credit resulting from a final and unappealable lawsuit. The organizational impact of this study affects the management of institutions and companies, allowing for a reduction in the asymmetry of economic and financial information and for promoting an improvement in the organizational management of companies. Originality: The originality of the study consists of the topic addressed and the form of its development, as no qualitative studies have been identified that have analyzed the requirements for the accounting recognition of an asset, more specifically a federal tax credit resulting from a lawsuit, to correlate them with the characteristics of a final and unappealable decision, in order to identify the time and the appropriate amount for the purposes of their accounting recognition. The issues explored in this work contribute to the decision-making by the company's management, allowing greater robustness in the decisions regarding the moment and the amount of the tax credit to be recognized in the accounting.